A constitutive model for 3D printed continuous fiber reinforced composite structures with variable fiber content. (15th May 2020) - Hou, Zhanghao; Tian, Xiaoyong; Zheng, Ziqi; Zhang, Junkang; Zhe, Lu; Li, Dichen; Malakhov, Andrei V.; Polilov, Alexander N.
Abstract: 3D printing provides a new technical means for the preparation of functionally controlled continuous fiber reinforced composites (CFRCs) with variable fiber content. The constitutive model of 3D printed CFRCs with different fiber contents are the basis for establishing mechanical analysis models and design methods of functionally regulated CFRCs based on 3D printing. In this paper, stiffness and strength properties of 3D printed CFRCs with different fiber contents were systematically studied, and the mapping relationship between material properties and fiber content was obtained. The failure processes of 3D printed CFRCs under different loads were studied by microstructural morphology and interfacial performance analysis, revealing the formation mechanisms of the material properties. The constitutive model and finite element analysis method of 3D printed CFRCs were established by using the material properties of 3D printed CFRCs with different fiber contents. The mechanical analysis mode was used to predict and analyze the performance of functionally graded CFRCs with variable fiber content. The results show that the mechanical analysis mode can be used for the optimization design and mechanical analysis of functionally controlled CFRCs.